Модификация критерия приведенных затрат электропривода для проектирования регулируемых асинхронных двигателей - Петрушин, Виктор Сергеевич; Еноктаев, Ростислав Николаевич (НТУ "ХПИ", 2014)
Предлагается модификация критерия приведенных затрат электропривода за счет использования коэффициента значимости эксплуатации, что позволяет согласовать максимум среднедиапазонного КПД и минимум среднедиапазонных приведенных затрат. В результате величина модифицированного критерия ПЗ меньше величины немодифицированного. Проведен анализ влияния коэффициента инфляции на критерий приведенных затрат. Его учет увеличивает величину модифицированного критерия ПЗ.

When designing an electric machine may be employed various design criteria, depending on the purpose and operating conditions of the EM. It is important in the design of energy-efficient AAM used as a design criterion of efficiency. Range of criteria does not account for the efficiency of the cost of construction and operation of the engine and drive the inflation rate and more. This accounting treatment is carried out by using the criterion of discounted costs. In order to use the modified criterion DC actuator must align its efficiency criterion, i.e. bring their extremes. To do this, use the boost factor operation Another important criterion for the introduction of a modified adjusted expenditures inflation factor, which takes into account the depreciation of the money supply process. As a result, value of the modified criterion given cost becomes less than the value of the unmodified.
Modification of the criterion of reduced expenditures for the design of controlled electric induction motors
Keywords: асинхронные двигатели; регулируемый асинхронный двигатель; оптимизационное проектирование; критерий приведенных затрат; модификация проектного критерия; коэффициент инфляции; инфляция; controlled induction motor; optimal design; criterion resulted expenses; modification of the design criteria; inflation factor